Implementasi Hak Anak yang Melakukan Tindak Pidana di Pengadilan Negeri Sidoarjo - Nikmah, Siti Khoirul (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2014)
Abstract: This article is a field research on âimplementation of childâs rights who conducts crime according to Undang-Undang No. 3 Tahun 1997 in Pengadilan Negeri of Sidoarjo on the Islamic criminal law perspectiveâ. This study aims to answer the questions about the implementation of the childâs rights who commits offense under Undang-Undang No. 3, tahun 1997 in Pengadilan Negeri of Sidoarjo and the view of the Islamic criminal law on the childâs rights who commits crime. To answer the two main questions, the author uses descriptive analysis method. The research shows that the implementation of the childâs rights who commits offense under Undang-Undang No. 3 tahun 1997 in Pengadilan Negeri of Sidoarjo during the process of examination in court are; entitling to an explanation of the procedure of the trial and the case, obtainning a legal counseling during the trial and a right to choose his own legal counsellor, communicating to his legal supervisor, getting an adequate facility in the trial, gaining protection against adverse actions, obtaining a right to express and defend his own opinion, getting a treatment as set out in the criminal code. In Islamic law, the judicial process of child who commits criminal acts is entitled to defense himself whether conducted by the child himself or his own legal counsellor and he also has right to ask a compensation for a wrong decision.Keywords: Childâs rights, crime, Undang-Undang, Islamic law.